Mix of trinexapac-ethyl and nitrogen application to reduce upland rice plant height and increase yield - Ferrari, Samuel [UNESP]; do Valle Polycarpo, Gustavo [UNESP]; Vargas, Pablo Forlan [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Luís Oliveira Cunha, Matheus [UNESP]; Pagliari, Paulo (Springer Nature, 2022)
Techniques to increase grain production such as nitrogen fertilization and plant growth regulators are essential to enable and enhance rice yield. Therefore, our goal was to evaluate the effect of nitrogen fertilization and application of trinexapac-ethyl on vegetative and reproductive traits of upland rice. Experiments were established in Registro, Brasil during the 2011 and 2014 growing seasons and treatments tested consisted of N rates (0; 50; 100; 150; and 200 kg N ha−1) and timings of TE application: V4, V7, R1 and control (without TE). Upland rice grain yield at N rates greater than 117 kg ha−1 applied as topdress combined with TE application at V7 will start to decrease grain yield. In addition, application of TE at V7 combined with N rates equal to or close to 117 kg ha−1 will lead to higher yields and shorter plants. The combination of N application at topdress combined with TE application at V4 led to a linear increase in the number of grains per panicle of rice plants. Nitrogen topdressing was found to increase plant height in the absence to TE or when TE is sprayed at V4 or R1. In addition, nitrogen topdressing had a positive increase in the number of tillers, stems, panicles, and SPAD index in rice plants.
Keywords: Fertilizing; Oryza sativa; Plant growth retardant